Foraging activity pattern and herbivory rates of the grass-cutting ant Atta capiguara - Caldato, N. [UNESP]; Forti, L. C. [UNESP]; Bouchebti, S.; Lopes, J. F. S.; Fourcassie, V. (Springer, 2016)
The objective of this study was to investigate the seasonal change in the pattern of foraging activity in the leaf-cutting ant Atta capiguara and to provide an estimate of the annual herbivory rate of its colonies. We surveyed at least once a month during 12 months, the foraging activity of two colonies located in a pasture of central Brazil. Each survey consisted in counting the number of ants exiting and returning (laden or unladen) to their nests during 10 min every hour during 24 h. The air temperature and relative humidity were noted at the beginning of each survey. Independent of the season, the colonies presented two peaks of foraging activity, one small peak at the beginning of the day and another peak at the end of the day. During the dry season, the diurnal activity ceased almost completely between 10:00 and 16:00. The proportion of ants returning to the nest laden with a leaf fragment was also lower than during the humid season. Activity rhythm depended significantly on both air temperature and humidity: foraging activity peaked when the temperature was around 25 A degrees C and relative humidity around 66 %. Based on the statistical model used to describe the activity rhythm, we estimated that over a period of 1 year, the total dry biomass of vegetation collected by the two colonies studied was, respectively, 25.16 kg for the bigger nest, and 11.69 kg for the smaller one, or an equivalent of 104.83-kg and 48.71-kg fresh biomass, respectively.
Keywords: Abiotic factors; Activity rhythm; Brazil; Foraging; Herbivory rate; Leaf-cutting ants